Effect of glutamine supplementation on exercise-induced changes in lymphocyte function - Krzywkowski, K.; Petersen, E. W.; Ostrowski, K.; Kristensen, J. H.; Boza, J.; Pedersen, B. K. (2001)
The purpose of this study was to investigate the possible role of glutamine in exercise-induced impairment of lymphocyte function. Ten male athletes participated in a randomized, placebo-controlled, double-blind crossover study. Each athlete performed bicycle exercise for 2 h at 75% of maximum O(2) consumption on 2 separate days. Glutamine or placebo supplements were given orally during and up to 2 h postexercise. The trial induced postexercise neutrocytosis that lasted at least 2 h. The total lymphocyte count increased by the end of exercise due to increase of both CD3(+)TCR alpha beta(+) and CD3(+)TCR gamma delta(+) T cells as well as CD3(-)CD16(+)CD56(+) natural killer (NK) cells. Concentrations of CD8(+) and CD4(+) T cells lacking CD28 and CD95 on their surface increased more than those of cells expressing these receptors. Within the CD4(+) cells, only CD45RA(-) memory cells, but not CD45RA(+) naive cells, increased in response to exercise. Most lymphocyte subpopulations decreased 2 h after exercise. Glutamine supplementation abolished the postexercise decline in plasma glutamine concentration but had no effect on lymphocyte trafficking, NK and lymphokine-activated killer cell activities, T cell proliferation, catecholamines, growth hormone, insulin, or glucose. Neutrocytosis was less pronounced in the glutamine-supplemented group, but it is unlikely that this finding is of any clinical significance. This study does not support the idea that glutamine plays a mechanistic role in exercise-induced immune changes. Am J Physiol Cell Physiol 2001 Oct;281(4):C1259-65